2010
DOI: 10.1007/s12187-010-9090-2
|View full text |Cite
|
Sign up to set email alerts
|

Who Matters for Children’s Early Development? Race/Ethnicity and Extended Household Structures in the United States

Abstract: Taking advantage of recent data that permit an assessment of the importance of extended household members in operationalizing the relationship between family structure and children’s early development, this study incorporated coresident grandparents, other kin, and nonkin to investigate the associations between extended household structure and U.S. children’s cognitive and behavioral outcomes at age 2. Analyses assessed whether these relationships differed for Latino, African American, and White children and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 40 publications
1
55
0
2
Order By: Relevance
“…Second, the datasets we examined lacked detailed information about family size at different points in the life course or about family members and family-like friends beyond parents, children, siblings, and spouses. In light of the important role of extended kin networks in black communities (39), future studies should collect information on a broader range of kin and kin-like ties that may contribute to additional death exposures for children raised by extended kin. Future work should also consider other forms of family member loss that vary by race and add to cumulative loss of family members; for example, black children are much more likely than white children to experience the effects of parental loss due to incarceration of the parent (40).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the datasets we examined lacked detailed information about family size at different points in the life course or about family members and family-like friends beyond parents, children, siblings, and spouses. In light of the important role of extended kin networks in black communities (39), future studies should collect information on a broader range of kin and kin-like ties that may contribute to additional death exposures for children raised by extended kin. Future work should also consider other forms of family member loss that vary by race and add to cumulative loss of family members; for example, black children are much more likely than white children to experience the effects of parental loss due to incarceration of the parent (40).…”
Section: Discussionmentioning
confidence: 99%
“…Using data found from The Early Childhood Longitudinal Study-Birth Cohort of 2001, Mollborn found having grandparent involvement and headed households can be helpful for the child's early and cognitive development (Mollborn et al, 2011). In a later study conducted by Mollborn (2012), an association was found between African American children living with a grandparent and higher cognitive scores, when compared to those living with only their parents.…”
Section: Grandparent Involvement Todaymentioning
confidence: 99%
“…Although nearly all research on family instability has focused on parental relationship changes as the source of instability, a growing number of scholars argue for a more comprehensive view of instability, capturing other types of household composition changes that are potentially consequential for children Mollborn, Fomby, and Dennis 2011;Warkentien, Condliffe, and DeLuca 2013). Prior research has investigated the consequences of extended family coresidence for children and the role that doubling up plays for families in need, suggesting that there may be meaningful consequences of instability in these households for children's outcomes.…”
Section: Motivation and Research Strategymentioning
confidence: 99%